Drug Utilization Review of Anesthetics in Surgery Department of Teritiary Care Hospitals of Warangal Region - Gajjala, Lakshmi Ravalitha; Adepu, Mounika; Dasari, Anuradha; Prusty, Korada Baikuntha; Arun, Gondi (Indian Journal of Pharmacy Practice)
Background: The concept of Drug utilization review lends its pivotal role in healthcare system in understanding, interpreting and improving the prescribing, administration and usage of drugs aiming to facilitate their rational use. This implies the prescription of a welldocumented drug in an optimal dose on the right indication within right period of time for right duration. Objective: To assess the use of anesthetics by different anesthesiologists within Warangal region and to evaluate the adopted anesthesia recording procedures. Materials and Methods: The study was a prospective observational study of anesthetic utilization which was carried out for 6 months in the department of Surgery in major tertiary care hospitals of Warangal after approval from institutional ethical committee. The data of patients who underwent surgery were collected in predesigned data collection form and were analyzed for drug utilization review and statistics were drawn descriptively. Results: 300 subjects who have undergone surgeries were enrolled for the study of these maximum of subjects being Adults (54%) within age group of 20-49. Of all planned surgeries (93%) and emergency surgeries (7%) were carried out and classified according to American Society of Anesthesiologists (ASA) grading. Local Anesthesia of which Spinal (78%) and Blocks (8%) was employed in major surgeries and General Anesthesia (14%) in few. Among General anesthetics, Propofol (P), Ketamine (K), Fentanyl (F), Midazolam (M), Suxinyl choline (SC), Vecuronium (V), Neostigmine (N), Thiopental (T) were used in combinations along with pre-anesthetic Glycopyrrolate (G). Combinations include GKV (7%), GFP (2%), GVN (2%), PKFM (3%) and VFTS (1%). Among Local Anesthestics, Bupivacaine (B), Lignocaine (L), Xylocaine (X) were used in combination or single. B (62%), BL (9%), X (8%) and B with Bupregesic (BPG) of (6%). Majorly, Open Reduction Internal Fixation with plates and screws (31), Open Reduction Internal Fixation with Dynamic Hip Screw (26), Lower Segment Cesarian Section (25), Urethroscopic Lithotripsy + Double J stenting (25), Hysterectomy (22), Hernioplasty (15) surgeries were carried out and many other surgeries of less frequency. Ceftriaxone (51%), Ranitidine (80%), Ketorolac (35%), Ondansetron (56%) were majorly prescribed post-operative drugs. Metronidazole (6%), Tetanus (6%), Amikacin (22%) were also prescribed additionally in few surgeries as post-operative drugs. Conclusion: Bupivicaine was most commonly prescribed for spinal. Propofol is most commonly prescribed drug for induction of anaesthesia followed by as maintenance of anaesthesia. Choices were contemplated rational as safety, efficacy and patient satisfaction were considered and outcomes were reliably good.
Keywords: Anesthesia; Utilization review; ASA grading; Warangal.